2014
DOI: 10.1136/bmjopen-2014-006442
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in long-term care facilities: a qualitative, multidisciplinary investigation

Abstract: ObjectivesTo explore healthcare professionals’ views of antibiotic prescribing in long-term care facilities (LTCFs). To use the findings to recommend intervention strategies for antimicrobial stewardship in LTCFs.DesignQualitative semistructured interviews were conducted. The data were analysed by thematic content analysis. After the interviews, the emerging findings were mapped to the theoretical domains framework (TDF), and the behaviour change wheel and behaviour change technique (BCT) taxonomy were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 24 publications
4
76
0
Order By: Relevance
“…While “nurses” are known to be important to the prescription of antibiotics [39, 40], we found that they helped to meet patients’ demands on hypnosedatives without consulting a doctor. According to a secondary data analysis of the French health insurance database, more than one third of Z-drug prescriptions were issued without a face-to-face consultation [41].…”
Section: Discussionmentioning
confidence: 95%
“…While “nurses” are known to be important to the prescription of antibiotics [39, 40], we found that they helped to meet patients’ demands on hypnosedatives without consulting a doctor. According to a secondary data analysis of the French health insurance database, more than one third of Z-drug prescriptions were issued without a face-to-face consultation [41].…”
Section: Discussionmentioning
confidence: 95%
“…13,38 However, NHs frequently do not have access to on-site physicians or advanced practice providers for NHs, and decisions to prescribe antibiotics are made remotely, thus relying heavily on nonprescriber NH staff assessment and interprofessional communication. 22,36,[39][40][41] In 2013-2014, a related national survey found that only about one-half (51%) of CMS-certified NHs collected data on antibiotic utilization and even fewer (46%) had written guidelines for antibiotic initiation. 42 These figures are expected to change as facilities work to meet new requirements.…”
mentioning
confidence: 99%
“…Flemming et al (Fleming, Bradley, Cullinan, & Byrne, 2014), in their study investigating healthcare professionals' views on antibiotic stewardship (over-prescribing) in long-term care facilities, combined the TDF with the COM-B and behaviour change technique taxonomy to map the in uential factors that contributed to the over-prescribing of antibiotics by doctors working in clinical areas. Participants (comprising doctors, pharmacists and nursing staff) identi ed several barriers that in uenced their prescribing practices: lack of knowledge, skills, inconsistency in individual practices, miscommunication and unsupportive workplace culture, all of which resonate with the ndings of our study.…”
Section: Discussionmentioning
confidence: 99%